Global earth mineral inventory: A data legacy. (11th November 2020) - Prabhu, Anirudh; Morrison, Shaunna M.; Eleish, Ahmed; Zhong, Hao; Huang, Fang; Golden, Joshua J.; Perry, Samuel N.; Hummer, Daniel R.; Ralph, Jolyon; Runyon, Simone E.; Fontaine, Kathleen; Krivovichev, Sergey; et al.
Abstract: Minerals contain important clues to understanding the complex geologic history of Earth and other planetary bodies. Therefore, geologists have been collecting mineral samples and compiling data about these samples for centuries. These data have been used to better understand the movement of continental plates, the oxidation of Earth's atmosphere and the water regime of ancient martian landscapes. Datasets found at 'RRUFF.info/Evolution' and 'mindat.org' have documented a wealth of mineral occurrences around the world. One of the main goals in geoinformatics has been to facilitate discovery by creating and merging datasets from various scientific fields and using statistical methods and visualization tools to inspire and test hypotheses applicable to modelling Earth's past environments. To help achieve this goal, we have compiled physical, chemical and geological properties of minerals and linked them to the above‐mentioned mineral occurrence datasets. As a part of the Deep Time Data Infrastructure, funded by the W.M. Keck Foundation, with significant support from the Deep Carbon Observatory (DCO) and the A.P. Sloan Foundation, GEMI ('Global Earth Mineral Inventory') was developed from the need of researchers to have all of the required mineral data visible in a single portal, connected by a robust, yet easy to understand schema. Our data legacy integrates these resources into a digestible format for exploration and analysis and has allowed researchers to gain valuable insights from mineralogical data. GEMI can be considered a network, with every node representing some feature of the datasets, for example, a node can represent geological parameters like colour, hardness or lustre. Exploring subnetworks gives the researcher a specific view of the data required for the task at hand. GEMI is accessible through the DCO Data Portal (https://dx.deepcarbon.net/11121/6200‐6954‐6634‐8243‐CC ). We describe our efforts in compiling GEMI, the Data Policies for usage and sharing, and the evaluation metrics for this data legacy. Abstract : The 'Global Earth Mineral Inventory' (GEMI) can be considered as a network with every node and edge representing some feature of the datasets. Exploring combinations of the network gives the researcher a particular view of the data required for the task at hand. We describe our efforts in compiling Global Earth Mineral Inventory, the Data Policies for usage and sharing and the completion and impact metrics for this Deep Carbon Observatory data legacy.